2022
DOI: 10.1007/s12144-022-03257-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise intensity and duration at a predetermined exercise volume on executive function among Apolipoprotein E (APOE)-ɛ4 carriers

Abstract: Emerging evidence indicates that acute exercise improves executive function, but its effects on higher-order executive functioning among people with a risk of Alzheimer's disease are not well understood. This study addressed the effects of acute exercise on the planning dimension of executive function among late middle-age adults who carried Apolipoprotein (APOE)-ɛ4. Exercise volume was kept constant, but exercise intensity and duration were manipulated. Eighteen adults in the age range 55-70 years who carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Similarly, Chang et al arrived at the same conclusion as Chen, highlighting that a 20 min session of physical exercise yields superior improvements in individuals' executive functions [24]. Another study by Chang et al demonstrated that there was no significant difference in the improvement of subjects' executive functions between exercise durations of 30 and 40 min, suggesting comparable effects [25].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, Chang et al arrived at the same conclusion as Chen, highlighting that a 20 min session of physical exercise yields superior improvements in individuals' executive functions [24]. Another study by Chang et al demonstrated that there was no significant difference in the improvement of subjects' executive functions between exercise durations of 30 and 40 min, suggesting comparable effects [25].…”
Section: Introductionmentioning
confidence: 81%
“…Post hoc comparative analysis, at time 1 and time 2, there were no significant differences (p > 0.05) between the high-intensity exercise groups (Group 3 (time 1: 579.32 ± 60. 25 S4). The main effect of exercise duration was not significant (F (3, 86) = 2.156, p = 0.117, η 2 = 0.005).…”
Section: Inhibition Controlmentioning
confidence: 98%